The Reformation and the Ten Commandments - Steinmetz, David Curtis 1936-2015 (1989)
Disagreement in the sixteenth century on the meaning of the First Commandment prompted dissension over such related issues as the nature of the Lord's Supper, the authority of the Old Testament for the church and the pace of ecclesiastical reform—issues that are still in dispute.